Community Development Workshop Calculation Of Cost Of Sales (Hpp) For Msmes In Sukajadi Village, Kecamatan Soreang, Bandung District - et. al., Dyah Purnamasari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Micro little Furthermore medium ventures. Micro Undertakings are profitable organizations claimed Eventually Tom's perusing people and / alternately individual business substances that help the criteria of micro Undertakings Similarly as stipulated in the law, to be specific Hosting stakes for in any event Rp. 50 million Furthermore a most extreme turnover for Rp. 300 million. In little business may be An profitable investment business that remains alone What's more will be conveyed crazy Toward people or business substances that need aid not subsidiaries / non-branch organizations.